Associations of a prognostic immune and nutritional index with all-cause and cause-specific mortality in individuals with depression: evidence from NHANES 2005–2018 - Fang, Wendong; Zhang, Jie; Gong, Wanxian; Xu, Yuanhong; Sun, Lei (Frontiers in Nutrition, 2025)
BackgroundThe prognostic immune and nutritional index (PINI) has been used to predict survival outcomes in colon cancer patients. However, the relationship between the PINI and survival outcomes in patients with depression remains unclear. This study aimed to explore the association of the PINI with all-cause and cause-specific mortality in patients with depression.MethodsThis study enrolled 6,610 patients with depression from the National Health and Nutrition Examination Survey (2005–2018). Mortality outcomes were determined by National Death Index records on 31 December 2019. Weighted Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for all-cause and cause-specific mortality. Kaplan–Meier curves were used to visualize survival probabilities at PINI levels, and subgroup analyses were performed to assess interactions with key variables. Smoothed curve fitting was also used to examine the non-linear relationship between the PINI and various mortality outcomes in the association.ResultsDuring a median follow-up of 6.5 years, a total of 702 all-cause deaths and 178 cardiovascular disease (CVD) deaths were recorded. Higher PINI quartiles were associated with lower all-cause, CVD, and cancer mortality (all P <0.001). Cox regression showed that the highest PINI quartile had significantly lower hazard ratios for all-cause mortality (HR = 0.458, 95% CI: 0.349–0.603), CVD mortality (HR = 0.258, 95% CI: 0.134–0.498), and cancer mortality (HR = 0.554, 95% CI: 0.284–1.081). A smooth curve fitting analysis revealed an L-shaped inverse relationship between the PINI and all-cause, CVD, and cancer mortality.ConclusionHigher PINI levels are associated with significantly lower all-cause and CVD mortality in individuals with depression. More large-scale and diverse population studies are needed to clarify the effects of higher PINI levels on all-cause and specific mortality.